2010
DOI: 10.1038/nchem.771
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced electrocatalysis of the oxygen reduction reaction based on patterning of platinum surfaces with cyanide

Abstract: The slow rate of the oxygen reduction reaction in the phosphoric acid fuel cell is the main factor limiting its wide application. Here, we present an approach that can be used for the rational design of cathode catalysts with potential use in phosphoric acid fuel cells, or in any environments containing strongly adsorbing tetrahedral anions. This approach is based on molecular patterning of platinum surfaces with cyanide adsorbates that can efficiently block the sites for adsorption of spectator anions while t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
292
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 303 publications
(305 citation statements)
references
References 39 publications
9
292
4
Order By: Relevance
“…This analysis suggests that extending the stability range of the non-hydrated phase will prove beneficial in improving the overall ORR activity. The importance of non-hydrated OH for the ORR at high potentials explains the enhanced ORR activity of Pt in hydrophobic ionic liquids 8 , in the presence of certain aqueous ions 6,7 and on stepped surfaces with narrow terrace width 9,10 . The last is unexpected as step sites strongly bind OH, as indeed observed with a reduced activity for small Pt nanoparticles 27 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This analysis suggests that extending the stability range of the non-hydrated phase will prove beneficial in improving the overall ORR activity. The importance of non-hydrated OH for the ORR at high potentials explains the enhanced ORR activity of Pt in hydrophobic ionic liquids 8 , in the presence of certain aqueous ions 6,7 and on stepped surfaces with narrow terrace width 9,10 . The last is unexpected as step sites strongly bind OH, as indeed observed with a reduced activity for small Pt nanoparticles 27 .…”
Section: Discussionmentioning
confidence: 99%
“…In general, dehydrated environments 8 will by their very nature limit the hydration of any OH intermediates. Finally, as hydrogen bonding of H 2 O to OH can compete with direct ion-OH interactions 28 , specific ions in the electrolyte could limit the hydration of OH 6,7 . This new insight into the subtle interplay between non-covalent hydrophobic and hydrophilic interactions can inspire the design of new catalysts, not only for the ORR but also for other relevant electrochemical reactions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this respect, the site blocking model gave a very elegant explanation for the different order in ORR activity when comparing low index Pt single crystal surfaces in sulfuric acid and perchloric acid electrolyte, respectively [1]. In addition it could explain the positive effect of adsorbed cyanide anions on the ORR activity in sulfuric and phosphoric acid electrolyte [21]. However, so far the experimental investigations have been performed under transient conditions, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that the PA is a key factor for the observed lower current densities in HT-PEMFCs, while especially the oxygen reduction reaction (ORR) taking place on the cathode is severely affected by the PA electrolyte. The inhibiting effect of the electrolyte on the ORR activity has been often explained by strong adsorption of PA ions on active catalyst sites [5][6][7][8][9]. We have recently demonstrated using cyclic voltammetry that adding even trace amounts of PA to electrolyte solutions that weakly interact with Pt-catalyst surfaces can lower the ORR catalytic activity by more than one order of magnitude [10].…”
Section: Introductionmentioning
confidence: 99%